Urbanization and growth of slums in Odisha: A geographical study of trends, patterns and regional concerns - Rekha Das,; Kapil Kumar Gavsker, (National Geographical Journal of India, 2025)
With increasing urbanization, the growth in size and density of the urban population has become an inevitable phenomenon, leading to the concentration of population in urban areas. The major drivers of urban population growth include natural increase, rural-to-urban migration, and census-related changes. The present study examines the trends and patterns of urbanization in Odisha during the period 2001–2011, with a particular focus on the contribution of net rural-to-urban migration. It also explores the underlying factors influencing migration and its role in urban growth across districts of the state. Additionally, the paper seeks to analyze the interlinkages between urbanization-led transition and the expansion of the slum population in Odisha. The study is based on secondary data sourced from the Census of India. Data analysis employs simple descriptive statistics such as percentages and proportions, along with statistical techniques including correlation and linear regression. Urban spatial patterns are illustrated using ArcGIS. The findings reveal significant regional variations in levels of urbanization, migration patterns, and their associated linkages with slum population growth in specific contexts within the state.